Insertion / Deletion DNA Polymorphisms in two South Indian Tribal Populations - P. Veerraju T.V. Rao N. Lakshmi, S. Reshmi1, Badal Dey and Partha P. Majumder (IJHG 1(2): 129-132 (2001), 2001)
DNA samples from 123 unrelated individuals belonging to 2 endogamous tribal populations, namely, the Koya Doras and Konda Reddis, of East Godavari District,Andhra Pradesh, South India were analysed for 8 human specific polymorphic insertion/deletion loci. Except Alu CD4, all the loci are polymorphic in both the populations. Most of the loci showed high levels of heterozygosity in both the populations. The average heterozygosity is higher in Konda Reddis than in Koya Doras. The results were compared with available Indian data on four other tribal populations, namely, Lodha, Munda, Santal and Tipperah.